ENHANCING STUDENTS' ACADEMIC ACHIEVEMENT THROUGH THE IMPLEMENTATION OF ADAPTIVE AND SUSTAINABLE CURRICULUM MANAGEMENT - Arifia Ika Fakhrina; Sukarman Sukarman; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the implementation of curriculum management in improving students' academic achievement. The study employed a qualitative approach using a library research design through the analysis of various relevant literature sources, including books and scholarly journal articles. The findings indicate that curriculum management, which encompasses systematic planning, implementation, and evaluation, plays a strategic role in enhancing the quality of learning and students' academic achievement. Curriculum planning that is responsive to students' needs, interests, and talents can create more relevant and effective learning experiences. Curriculum implementation supported by teachers' competencies and the integration of enrichment programs such as academic competitions, research activities, and other scholarly programs has been shown to improve students' academic performance. Furthermore, continuous curriculum evaluation serves as a reflective mechanism for improving the learning process and ensuring alignment between educational goals and outcomes. Therefore, integrated and adaptive curriculum management is a key factor in creating a competitive educational ecosystem and optimally supporting the enhancement of students' academic achievement.